2019
DOI: 10.3390/surfaces2020019
|View full text |Cite
|
Sign up to set email alerts
|

Interface Behaviour and Work Function Modification of Self-Assembled Monolayers on Sn-Doped In2O3

Abstract: The modification of the work function of Sn-doped In 2 O 3 (ITO) by vacuum adsorption of 4-(Dimethylamino)benzoic acid (4-DMABA) has been studied using in situ photoelectron spectroscopy. Adsorption of 4-DMABA is self-limited with an approximate thickness of a single monolayer. The lowest work function obtained is 2.82 ± 0.1 eV, enabling electron injection into many organic materials. In order to identify a potential influence of the ITO substrate surface on the final work function, different ITO surface orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“… 2 However, the work function of SAM-functionalized ITO has also been found to be sensitive to the UV–O 3 treatment time. 9 A report using 2PACz SAM also demonstrated that the performance of organic solar cells depended on the duration of O 2 -plasma treatment preceding SAM deposition. 10 Since the hydroxyl group concentration on any surface is a key element for promoting SAM formation via covalent bonds, 11 , 12 hydroxyl group rich NiO processed by atomic layer deposition (ALD) is expected to promote controlled and homogeneous SAM formation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“… 2 However, the work function of SAM-functionalized ITO has also been found to be sensitive to the UV–O 3 treatment time. 9 A report using 2PACz SAM also demonstrated that the performance of organic solar cells depended on the duration of O 2 -plasma treatment preceding SAM deposition. 10 Since the hydroxyl group concentration on any surface is a key element for promoting SAM formation via covalent bonds, 11 , 12 hydroxyl group rich NiO processed by atomic layer deposition (ALD) is expected to promote controlled and homogeneous SAM formation.…”
Section: Introductionmentioning
confidence: 98%
“…Al-Ashouri et al reported that UV–O 3 was essential for surface activation of ITO for SAM formation in perovskite solar cells . However, the work function of SAM-functionalized ITO has also been found to be sensitive to the UV–O 3 treatment time . A report using 2PACz SAM also demonstrated that the performance of organic solar cells depended on the duration of O 2 -plasma treatment preceding SAM deposition .…”
Section: Introductionmentioning
confidence: 99%
“… 52 Another theory that may elucidate the phenomenon of crystalline orientation’s influence on local WF variation is the surface polarity concept, introduced by Tasker. 53 While the initial observations were for In 2 O 3 , 52 , 54 , 55 this concept can be extended to ITO. In detail, the (111) plane is a Tasker II type of surface without surface dipole perpendicular to the surface normal.…”
Section: Methodsmentioning
confidence: 99%